Asymptotic solutions of a system of differential equations with multiple turning point - Klyuchnyk, I. H. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
Using a transformation matrix, we asymptotically reduce a system of differential equations with a small parameter in the coefficients of a part of derivatives and with multiple turning point to an integrable system of equations.